Advances in the synthesis of glycosidic macrolides: clavosolides A–D and cyanolide A. Issue 12 (12th September 2016) - Lee, Kiyoun; Lanier, Megan L.; Kwak, Jae-Hwan; Kim, Hyoungsu; Hong, Jiyong
Abstract : This review covers the isolation, structure determination, biological activity, and synthesis of clavosolides A–D and cyanolide A. Abstract : Covering: 2005 to 2016 Clavosolides A–D and cyanolide A are glycosidic macrolides and represent a new family of marine natural products. They possess a number of unusual structural features and have attracted considerable interest from the synthetic community. This review presents a comprehensive survey of all aspects of the clavosolides A–D and cyanolide A. Specific topics include isolation, structure determination, biological activity, and synthetic approaches.